2015
DOI: 10.4103/0975-7406.155934
|View full text |Cite
|
Sign up to set email alerts
|

One point fixation of zygomatic tripod fractures in the zygomatic buttress through Keen′s intraoral approach: A review of 30 cases

Abstract: For decades, facial beauty and esthetics have been one of the most important quests of the human race. The lateral prominence and convexity of the zygomatic bone makes it the most important bone for providing the aesthetic facial look and sets up the facial width but at the same time this prominence and convexity makes this bone more vulnerable to injury. Zygomatic complex fractures or tripod fractures are the second most common fractures after nasal fractures among facial injuries. Several studies have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
(14 reference statements)
0
21
0
4
Order By: Relevance
“…Open reduction of zygomatic complex fractures solely by an intraoral surgical approach has previously been described in the literature [9 -17]. Thirty patients with zygomatic complex fractures were treated with an intraoral approach and one point fixation at the zygomaticomaxillary buttress [16]. Clinical and radiographic evaluation disclosed no paresthesia, pain or cosmetic disfiguration after six months.…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction of zygomatic complex fractures solely by an intraoral surgical approach has previously been described in the literature [9 -17]. Thirty patients with zygomatic complex fractures were treated with an intraoral approach and one point fixation at the zygomaticomaxillary buttress [16]. Clinical and radiographic evaluation disclosed no paresthesia, pain or cosmetic disfiguration after six months.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that non-comminuted tripod fractures with mild or no displacement can be stabilized with a single-point fixation in the FZ area, without any diplopia or enophthalmos. The zygoma provides the attachment point for muscles of mastication and facial animation, and it withstands the forces of contraction of the masseter muscle 41 . Fujioka et al 42 demonstrated that 1-point fixation gives 3-point alignment and rigidity for non-comminuted fractures.…”
Section: Open Methods Of Reduction and Fixation: Surgical Approacmentioning
confidence: 99%
“…The incidence of ZMC fractures varies with geographical location, socioeconomic trends, and incidence of road traffic collisions (RTCs), alcohol abuse and drug abuse [4] . A number of studies had shown ZMC fractures to be the second most common facial fracture, after nasal bone or mandible fractures [3][4][5][6] . Common causes of ZMC fractures include interpersonal violence (15%-64.5%), RTCs (13.9%-49%), as well as falls, occupational accidents, and sport-related injuries [3,7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…An intact zygoma (or zygomatic bone) and its surrounding bony anatomy are essential for maintaining facial contour, such as cheek prominence, as well as orbital integrity [5] . Anatomically, the zygoma is attached to the frontal bone (via the frontozygomatic suture), the maxilla (via the zygomaticomaxillary suture), the squamous part of the temporal bone (via the zygomaticotemporal suture) and the sphenoid bone (via the zygomaticosphenoid suture) [ Figure 1] [6] . Fractures that involve the zygoma often occur at these four suture sites, leading to a "tetrapod" fracture pattern, known as a "zygomatic complex fracture" (ZMC).…”
Section: Introductionmentioning
confidence: 99%